Changes of endogenous enzymes and physiochemical indicators in the process of dry-salted Decapterus maruadsi. Issue 1 (1st January 2019) - Wu, Yan Yan; Cao, Song Min; Yang, Shao Ling; Hu, Xiao; Lin, Wan Ling; Yang, Xian Qing; Rong, Hui
ABSTRACT: In order to evaluate the relationship between of endogenous enzymes and physiochemical indicators during the processing of dry-salted Decapterus maruadsi produced by the traditional method. The evolution of the endogenous enzymes (cathepsin B, cathepsin L, cathepsin H, acid lipase, neutral lipase, and phospholipase) and physical and chemical parameters (moisture content, salt content and pH) of dry-salted Decapterus maruadsi during processing were investigated. Principal component analysis and Pearson correlation coefficient analysis were used to explore the main factors influencing the endogenous enzyme activity and the interactions between endogenous enzymes. The following results were observed during the processing of dry-salted Decapterus maruadsi : the salt content could stimulate cathepsin (L and B) activity and inhibit lipase activity; a lower moisture content could inhibit lipase activity, while the inhibitory effect on cathepsin was inconspicuous; pH had a minor influence on the endogenous enzyme activities; cathepsin B and L could partially inhibit lipase activity.